The Influence Of Digital Marketing On Competitive Advantage And Performance of Micro, Small And Medium Enterprises - Asikin, Muhamad Zaenal; Fadilah, Muhamad Opan; Saputro, Wahyu Eko; Aditia, Oriza; Ridzki, Mohamad Maulana (Ridwan Institute, 2024)
This study aimed to determine the influence of Digital Marketing on Competitive Advantage and MSME Performance. The research employed a Quantitative Method utilizing SPSS and SEM (Structural Equation Model) assisted analysis tools with the Lisrel program. The analysis results reveal that digital marketing exerts a positive and significant effect on competitive advantage, digital marketing significantly impacts MSME performance positively, competitive advantage significantly influences MSME performance positively, and Digital Marketing positively affects MSME performance through competitive advantage.